Save a Child: Know How to Identify and Report Child Abuse - Andrew E. Toelle; Kate Fogarty (EDIS)
Revised! FCS2119, a 5-page fact sheet by Andrew E. Toelle and Kate Fogarty, discusses child abuse laws and procedures for reporting abuse. It also contains information about different types of abuse and how to identify abused or neglected children. Includes references. Published by the UF Department of Family Youth and Community Sciences, November 2008.